A Critical Analysis of Constitutional Court Justices' Terms of Office: A Rule of Law Perspective - Nabila, Alya Putri (CV. Era Digital Nusantara, 2024)
Abstract: The revision of Law Number 7 of 2020, concerning the Third Amendment, to Law Number 24 of 2003, concerning the Constitutional Court, has sparked controversy in the community. Where the substance of the regulation since the first revision until now has always seemed to only tinker with the technical realm and the periodisation of the term of office of MK judges. The public has drawn attention to the closed and hasty nature of the formulation process. This has given rise to a long debate among the community regarding the potential threat to judicial independence, where the changes made are considered to be able to influence the decision-making process of MK judges. In the context of a state of law, changes to the regulation of the term of office of MK judges should consider the principles of justice and transparency to maintain the integrity of the judicial institution. To make sure that the judicial power can work independently and objectively, in line with democratic values, it is important to have rules that are clear and fair. Open and collaborative dialogue between the government, legislative institutions, and civil society is essential to creating regulations that are not only technical but also reflect the aspirations of the community and uphold the principles of justice and transparency as studied in the concept of a state of law. Purpose: This research aims to comprehensively analyse how the current MK judges' tenure arrangements are based on the principles of the rule of law. This research study explores the legal framework governing the tenure of MK judges, as well as the implications of these arrangements for the independence and accountability of the judicial institution. In addition, this study is expected to provide an in-depth analysis of legal issues related to the tenure of MK judges. Design/Methodology/Approach: This study is a normative legal analysis focused on identifying relevant legal rules, principles, and doctrines to address pressing legal issues. To achieve this, the research employs several methodologies, including a legislative approach, a conceptual approach, and a case-based approach. By utilizing these diverse methods, the research aims to thoroughly examine the implications of the current regulations governing the terms of office for MK judges on the principles of independence and accountability. These principles are essential ideals within the framework of a rule-of-law state, emphasizing the need for a renewable commitment to uphold judicial integrity and public trust. In addition, this research will also explore the impact of these regulations on public trust in judicial institutions. Findings: In this research, it was found that the substance of the MK judges' term of office regulated in Law Number 7 of 2020 does not reflect the principle of a state of law, which should be the theoretical basis in the process of draughting legal regulations. One of the main problems identified is the inconsistency in the draughting of articles relating to the period of the MK judges' term of office. This uncertainty creates confusion and the potential for abuse of power, as well as concerns that the decision-making of MK judges can be caused by political intervention alone. In addition, the process of drafting Law Number 7 of 2020 is considered too hasty and closed. This further worsens the legitimacy of the law and raises doubts among the public. Originality/value: This research emphasises the importance of legal certainty that supports the principle of independence in judicial power. This research highlights the importance of term office arrangements that not only guarantee stability but also protection against intervention from political power. Judges' terms of office that are too short or dependent on external influences can risk eroding public trust in the integrity of the judicial institution. In this context, this research provides insight that optimal arrangements must be based on the principle of a state of law in order to maintain a balance between stability and independence, to create a strong foundation for justice and legal order.